2021
DOI: 10.3389/fpubh.2021.671988
|View full text |Cite
|
Sign up to set email alerts
|

Supporting Child Development Through Parenting Interventions in Low- to Middle-Income Countries: An Updated Systematic Review

Abstract: Background: Over 250 million children in low- and middle-income countries are at risk of not achieving their fullest developmental potential due to co-occurring risks such as poor nutrition and inadequate learning opportunities. Early intervention programs integrating the aspects of nurturing care, that is, good health, adequate nutrition, safety and security, responsive caregiving, and learning opportunities, may ameliorate against the negative impact of these adverse conditions.Methods: This meta-analytic re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
35
0
8

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 49 publications
(43 citation statements)
references
References 90 publications
0
35
0
8
Order By: Relevance
“…Next, a more nuanced understanding regarding how specific contexts contribute to specificities in social-emotional growth is warranted, acknowledging the heterogeneity both within specific groups (Chen et al, 2021;Lin et al, 2021) and across cultural frameworks (Oh et al, 2021;Rothenberg et al, 2021), as well as considering moderators of cultural effects on socialemotional development (Davidov et al, 2021). Indeed, the transferability of parenting interventions aimed at nurturing child development across contexts depends on how well such interventions (including their curriculums and assessment tools) are adapted to the local context (Jeong et al, 2018;Zhang et al, 2021), as well as the extent to which bottom-up, community-based approaches (involving all stakeholders) are used to identify and prioritize the needs of a specific group (Abubakar et al, 2019;Speidel et al, 2021).…”
Section: Com Plem En Ta R I T Y a N D I N T Erv En T Ions A I M Ed At N U Rt U R I Ng Soc I A L -E Mot Iona L Dev E Lopm E N Tmentioning
confidence: 99%
“…Next, a more nuanced understanding regarding how specific contexts contribute to specificities in social-emotional growth is warranted, acknowledging the heterogeneity both within specific groups (Chen et al, 2021;Lin et al, 2021) and across cultural frameworks (Oh et al, 2021;Rothenberg et al, 2021), as well as considering moderators of cultural effects on socialemotional development (Davidov et al, 2021). Indeed, the transferability of parenting interventions aimed at nurturing child development across contexts depends on how well such interventions (including their curriculums and assessment tools) are adapted to the local context (Jeong et al, 2018;Zhang et al, 2021), as well as the extent to which bottom-up, community-based approaches (involving all stakeholders) are used to identify and prioritize the needs of a specific group (Abubakar et al, 2019;Speidel et al, 2021).…”
Section: Com Plem En Ta R I T Y a N D I N T Erv En T Ions A I M Ed At N U Rt U R I Ng Soc I A L -E Mot Iona L Dev E Lopm E N Tmentioning
confidence: 99%
“…Formative research was conducted to inform the community engagement and ECD intervention implementation processes. The formative research involved a systematic review of parenting interventions on stimulation and responsive caregiving for children under age 2 years in low- and middle-income countries [ 31 ]. Furthermore, between May and June 2018, a household survey was conducted among 458 Kenyan and 118 immigrant households on nurturing care among caregivers of children aged 0–2 years in Dagoretti’s informal settlements [ 32 ], and a qualitative study involving 14 focus group discussions with Kenyan and refugee caregivers on ECD practices and experiences [ 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…The findings from the systematic review indicated that parenting interventions, which encourage nurturing care effectively improve children’s cognitive, language, motor, and social-emotional development. Moreover, these interventions are most beneficial when delivered in group sessions or group sessions combined with home visits, and are also feasible and effective when delivered by trained paraprofessionals [ 31 ]. These findings indicate that parenting interventions with nurturing care components are feasible for the promotion of early child development in low-income settings.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, cash-transfer programmes showed to have an impact in improving youth mental health and fostering development[131][132][133][134], and housing assistance programs also presented benefits[135,136]. Moreover, studies on community intervention revealed benefits at a group level, as shown by neighbourhood empowerment programs and parenting interventions delivered by community members[137][138][139][140][141][142]. In line with current recommendations, interventions should seek to be culturally sensitive and promote active involvement of participants[138,[143][144][145][146].…”
mentioning
confidence: 98%